Description of Psidium brevipedunculatum (Myrtaceae), and considerations about the high diversity and endemism for the genus Psidium from Bahia, Brazil - Tuler, Amélia Carlos; de Faria, Jair Eustáquio Quintino; Landrum, Leslie Roger (Phytotaxa, 2020)
Increased sampling in under-collected areas and the digitization of herbarium collections have led to recent findings revealing the high diversity and endemism of the genus Psidium in the state of Bahia. This paper describes a new species of Psidium (Myrtaceae, Myrteae) occurring in the Caatinga biome of Bahia in Northeastern Brazil. It is a shrub or small tree up to 1.5–5 m tall, with of short peduncles (1.5–5 mm long), blades elliptic to obovate, apex with a cuspidate tip, lower leaf surfaces densely tomentose, hairs yellowish brown. The calyx is closed and tears irregularly. An illustration and comments about morphology, distribution and threats are provided.